Studi Historis: Sistem Sosial Dan Pendidikan Arab Pra-Islam - Hamam Aqil Barid; Kholid Mawardi (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
This article explores the complex fabric of pre-Islamic Arab society, focusing on its sociopolitical structure, cultural identity, belief systems, and educational practices. Known as the Jahiliyyah period, this era was marked by tribal loyalty, oral poetry, and the absence of centralized governance. Social life revolved around kinship and clan-based honor, often resulting in inter-tribal conflicts and deeply rooted patriarchy. Despite the perception of ignorance, Arab society possessed rich oral traditions, with poetry, genealogy, and storytelling serving as primary vehicles of knowledge transmission. Formal education was largely nonexistent; literacy was confined to a select few in urban centers such as Mecca and Yaman. Most educational experiences were informal and utilitarian, shaped by the desert environment and nomadic lifestyle. This study examines how the lack of organized educational institutions reflected and reinforced social hierarchies and tribal values. Moreover, it reveals how cultural and environmental factors influenced both the intellectual landscape and the character of the Arabian people, laying the foundation for the profound transformation brought by Islam.